2012
DOI: 10.1890/11-0892.1
|View full text |Cite
|
Sign up to set email alerts
|

From metamorphosis to maturity in complex life cycles: equal performance of different juvenile life history pathways

Abstract: Performance in one stage of a complex life cycle may affect performance in the subsequent stage. Animals that start a new stage at a smaller size than conspecifics may either always remain smaller or they may be able to "catch up" through plasticity, usually elevated growth rates. We study how size at and date of metamorphosis affected subsequent performance in the terrestrial juvenile stage and lifetime fitness of spadefoot toads (Pelobates fuscus). We analyzed capture-recapture data of >3000 individuals samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 51 publications
9
59
0
Order By: Relevance
“…Our results indicate that survival differs between ontogenetic stages and that the survival rate increases with age. This is in accordance with previous studies suggesting that post‐metamorphosis survival is positively correlated with age and size in vertebrates (Stearns, ), and especially in amphibians (Altwegg & Reyer, ; Schmidt, Hödl & Schaub, ). In the latter, larger and older individuals outperform smaller and younger ones in osmoregulation and hydroregulation performance (Wells, ), which decreases mortality risks and the cost of biological functions such as dispersal.…”
Section: Discussionmentioning
confidence: 98%
“…Our results indicate that survival differs between ontogenetic stages and that the survival rate increases with age. This is in accordance with previous studies suggesting that post‐metamorphosis survival is positively correlated with age and size in vertebrates (Stearns, ), and especially in amphibians (Altwegg & Reyer, ; Schmidt, Hödl & Schaub, ). In the latter, larger and older individuals outperform smaller and younger ones in osmoregulation and hydroregulation performance (Wells, ), which decreases mortality risks and the cost of biological functions such as dispersal.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, in vertebrates including amphibians catch-up growth is associated with permanently altered HPI axis activity and may be related to differing coping styles to extrinsic stressors [60], [64]. Another intrinsic factor that may be related to these hatching time, development and growth patterns is sex [65]. Studies of birds have found hatching to differ among the sexes and to potentially be an adaptive maternal effect [49][51].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while larval life stages may be viable targets for remediation, preservation of sufficient high-quality adult habitat remains critical (Harper et al 2008) and additional experiments examining effects of contaminants on terrestrial adult amphibians are needed (Hopkins and Rowe 2010). Moreover, because reductions in body size are a common sublethal effect of contaminants (Boone and Bridges 2003) that may persist into terrestrial life stages (Todd et al 2012), future studies should rigorously evaluate size-specific survival of amphibians in field (e.g., Schmidt et al 2012). Finally, our study provides a habitat-based framework (Akcakaya 2000) for incorporating environmental stochasticity into models of population-level responses of amphibians to ecological or environmental stressors.…”
Section: Discussionmentioning
confidence: 99%